A Study of Methylene Blue Dye Interaction and Adsorption by Monolayer Graphene Oxide. (9th August 2022) - Ederer, Jakub; Ecorchard, Petra; Slušná, Michaela Šrámová; Tolasz, Jakub; Smržová, Darina; Lupínková, Simona; Janoš, Pavel
Abstract : The graphene oxide (GO) interaction with methylene blue (MB) cationic dye was studied in an aqueous solution at different pH during MB adsorption. The mutual interaction of MB with GO surface was studied and evaluated by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). The π - π and electrostatic interaction of MB with GO surface are the main types of interactions, and the XRD data show the monomeric arrangement of MB cation with GO. The GO surface functional groups and point of zero charge (PZC) were determined by acid-base titration. Suitability of zeta-potential measurement and acid-base titration method was briefly discussed. The quality of prepared GO was evaluated by Raman spectroscopy, XRD, and atomic force microscope (AFM). The experimental adsorption equilibrium data were analyzed using Langmuir, Langmuir-Freundlich, Freundlich, and Temkin isotherms. The GO maximum adsorption capacity increases with higher pH, that is ascribed to the facile interaction of negatively charged GO with positively charged MB structure.